From exclusion to inclusion in old age : a global challenge - Scharf, Thomas; Keating, Norah Christine (Ageing and the lifecourse., 2012)
Taking a broad international perspective, this highly topical book casts light on patterns and processes that either place groups of older adults at risk of exclusion or are conducive to their inclusion.